Full‐Genome Sequence of Porcine Circovirus type 3 recovered from serum of sows with stillbirths in Brazil. Issue 1 (12th October 2017) - Tochetto, C.; Lima, D. A.; Varela, A. P. M.; Loiko, M. R.; Paim, W. P.; Scheffer, C. M.; Herpich, J. I.; Cerva, C.; Schmitd, C.; Cibulski, S. P.; Santos, A. C.; Mayer, F. Q.; et al.
Summary: Two full‐genome sequences of porcine circovirus type 3 (PCV3) are reported. The genomes were recovered from pooled serum samples from sows who had just delivered litters with variable numbers of stillbirths. The two circular genomes (PCV3‐BR/RS/6 and PCV3‐BR/RS/8) are 2, 000 nucleotides long and contain two open reading frames (ORFs) oriented in opposite directions that encode the putative capsid (Cap) and replicase (Rep) proteins. The intergenic region contains a stem‐loop motif, as reported for other circoviruses. Rolling circle replication motifs and putative helicase domains were identified in the Rep coding region. The degree of overall nucleotide similarity between the genomes reported here and those available at GenBank was higher than 97%. No PCV3 sequence was detected in pooled serum samples from sows which had no stillbirths on the same farms. However, further studies are necessary to confirm the association between PCV3 and the occurrence of stillbirths.